Installation of RC column / Nurul Izzati Abd Rahim - Abd Rahim, Nurul Izzati (Universiti Teknologi MARA UiTM,Perak, 2020)
Energy is a very important thing to elaborate, therefore this report will discuss about energy efficiency for the building envelope based on Code of Practice on Energy Efficiency and Use of Renewable Energy for Non-Residential Building MS 1525: 2007. This report was conducted for the building envelope at Library of UiTM Perak and Main Library of UM. The objective of this report is to compare the capacity of two educational buildings and how far it fulfills the requirements in the guideline. It will focus on energy conservation that provides a comfortable environment for its occupants. To illustrate the function of building envelope as an important aspect to focus on building surface design achievement and then to evaluate how far the potential of the building envelope that could fulfill the building criteria that is prescribed by the requirements in the guideline based on U Value and OTTV Value. This report will also look at the energy efficiency management based on the guideline by producing the use of effective and continuous energy and to evaluate the quality of energy usage by creating energy efficient environment that gives a better impact for the National Energy Sector in the future.